Improvement of Surface Roughness of Stainless Steel AISI 316L by Electrical Discharge Machining Process - Dr. Abdulaziz Moftah Abodena (African Journal of Advanced Pure and Applied Sciences, 2024)
The manufacturing industries are using more high-strength, high-hardness materials as a result of technological advancements. More sophisticated techniques including electro-discharge machining (EDM), ultrasonic machining (USM), electric chemical machining (ECM), and laser machining are gradually replacing conventional industrial processes in the machining of these materials. By selecting the right machining parameters to efficiently control the amount of material removed, EDM can create intricate and precise parts with ease. Larger and deeper discharge craters are produced by rough machining conditions because a significant amount of the melted material is removed, even though EDM can achieve accurate dimensions and fine surface integrity under finishing conditions. This study aims to identify the best process parameter settings for electro-displacement machining (EDM) of stainless steel AISI 316L when the material is processed on a rough surface. FORM 2-LC machine was used for the trials, and the Taguchi approach was applied. The Taguchi approach is utilized to design the experimental setup, examine how each parameter affects the machining characteristic, and forecast which EDM parameter is best. The process parameters that have a significant impact on the performance attributes and the percentage contribution of surface roughness are examined using analysis of variance (ANOVA). Controlling the level of the machining variables is generally found to enhance the average surface roughness. For instance, when the current is at its lowest, pulse on is at its medium, and pulse off is at its maximum, the optimal value of roughness can be achieved.